2021
DOI: 10.1136/bmjgh-2020-004145
|View full text |Cite
|
Sign up to set email alerts
|

State of the evidence: a survey of global disparities in clinical trials

Abstract: IntroductionIdeally, health conditions causing the greatest global disease burden should attract increased research attention. We conducted a comprehensive global study investigating the number of randomised controlled trials (RCTs) published on different health conditions, and how this compares with the global disease burden that they impose.MethodsWe use machine learning to monitor PubMed daily, and find and analyse RCT reports. We assessed RCTs investigating the leading causes of morbidity and mortality fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The results indicated that only a small percentage (7.5%) of health data records had received documented citations by scientific publications. We find the level of data sharing and reuse varies across diseases, just like the imbalance of clinical trials across diseases found by (Marshall et al, 2021). Most recently, Zuo et al (2021) provided a review on novel coronavirus disease (COVID-19) datasets extracted from PubMed Central articles.…”
Section: Discussionmentioning
confidence: 92%
“…The results indicated that only a small percentage (7.5%) of health data records had received documented citations by scientific publications. We find the level of data sharing and reuse varies across diseases, just like the imbalance of clinical trials across diseases found by (Marshall et al, 2021). Most recently, Zuo et al (2021) provided a review on novel coronavirus disease (COVID-19) datasets extracted from PubMed Central articles.…”
Section: Discussionmentioning
confidence: 92%
“…Although an increasing amount of biomedical research is coming out of Asia, ASEAN is dwarfed by output from China, Japan, and Korea, due to an amalgam of forces that include limited resources overall and lower priority given to research by national/government funding agencies. 40 Meta-science research may aid in quantifying research disparities and identifying areas of need. A recent study of stroke research from Southeast Asia found that over 40% of studies came from Singapore.…”
Section: Factors Contributing To Disparities In Access To Cancer Diag...mentioning
confidence: 99%
“…Additionally, rural Appalachians have a higher percentage of later‐stage diagnoses than their urban counterparts, which contributes to increased mortality rates 7 . These disparities are linked to conditions, such as increased tobacco use 8 and obesity, 9,10 as well as social determinants of health like poverty, 10 decreased educational attainment and cancer literacy, 11–14 and decreased access to health care resources 15 …”
Section: Introductionmentioning
confidence: 99%